Factors associated with Nugent-bacterial vaginosis in pregnancy and postpartum among women in rural northwestern Bangladesh. - Lena Kan; Susan Tuddenham; Parul Christian; Allan Massie; Alain B Labrique; Lee Wu; Hasmot Ali; Mahbubur Rashid; Ethan Gough; Subhra Chakraborty; Michael T France; Jacques Ravel; et al. (PLOS Global Public Health)
Community-based longitudinal data on factors linked to bacterial vaginosis (BV) during and after pregnancy in Bangladesh are limited. Using data from a rural randomized trial of vitamin A and β-carotene supplementation, we examined factors associated with Nugent-score-assessed BV. Self-collected vaginal swabs from 1,812 participants were obtained in early pregnancy, late pregnancy, and 3 months postpartum for Nugent scoring. We analyzed associations between participant factors and Nugent-BV (scores 7-10 vs. 0-6; 4-10 vs. 0-3) at each time point. Bivariate associations were tested using chi-square and t-tests, and multivariable log-binomial regression was used to estimate adjusted prevalence ratios with 95% confidence intervals. In early pregnancy, consistent soap use during bathing (vs. never/sometimes) was associated with a decreased risk of Nugent-BV 7-10 (adjusted prevalence ratio (aPR): 0.64, 95% CI: 0.43, 0.96). In late pregnancy, Hindu religion (vs. Muslim) (aPR: 2.68, 95% CI: 1.52, 4.72) and higher gestational age (aPR: 1.18, 95% CI: 1.04, 1.35) were associated with increased risk of Nugent-BV 7-10 and 4-10. Furthermore, maternal underweight (BMI < 18.5 kg/m² vs. ≥ 18.5) (aPR: 0.62, 95% CI: 0.44, 0.87) and having ≥1 antenatal care visit (vs. none) (aPR: 0.59, 95% CI: 0.38, 0.91) were associated with reduced risk of Nugent-BV 4-10. Among multiparous individuals, a longer pregnancy interval of ≥18 months (vs. < 18 months) was protective against Nugent-BV 7-10 (aPR: 0.34, 95% CI: 0.14, 0.81). At 3-months postpartum, vitamin A supplementation (vs. placebo) was associated with a decreased risk of Nugent-BV 7-10, consistent with prior trial findings. Our findings indicate that Nugent-BV during pregnancy and postpartum is linked to modifiable factors, including hygiene, nutrition, birth spacing, and healthcare access. Rigorous randomized trials are needed to evaluate their ability to reduce BV, promote long-term vaginal health, and lower the risk of adverse pregnancy outcomes.